Evaluation of factors related to postoperative mortality in patients who underwent pancreatoduodenectomy due to periampullary region tumors - Bahadir Arikan, Turkmen; Mutevelli Sozuer, Erdogan; Topal, Ugur; Dal, Fatih; Kubra Bozkurt, Gamze (Annals of Medical Research, 2021)
Aim: In this study, we aimed to investigate the factors related to postoperative mortality after pancreatoduodenectomy in our clinic.Materials and Methods: Patients who underwent pancreatoduodenectomy due to a periampullary region tumor between 2010 and 2019 were included in the study. Mortality that occurred within 30 days after PD was defined as postoperative mortality and groups were formed according to this definition Group 1(Postoperative Mortality) and Group 2(No mortality). The demographic and clinical features, laboratory parameters, and tumor features of the patients were compared between the groups. Risk factors for mortality were analyzed by univariate analysis and multivariate logistic regression analysis.Results: 155 patients participated in our study. We found our postoperative mortality rate as 11.6%. Accordingly, Group 1 consisted of 18 and Group 2 consisted of 137 patients. The sex was similar (p: 0.235). The average age was higher in Group 1 than 2 (71.2 vs 63.7, p:0.013). Tumor localizations were similar in groups (p:0.275). Lymph node positivity was similar in the groups (50% vs 41.6%, p:0.333). The pancreatic fistula was higher in Group 1, but not statistically significant (33% vs 18.2%, p:0.119). Preoperative white blood cell count (9490 mm3 vs 8050 mm3) and neutrophil count (6898 mm3 vs5442 mm3) were higher in Group 1. In multivariate analysis, no parameters were single-handedly risk factors. Conclusion: No factor was found to be effective alone in the development of mortality after pancreaticoduodenectomy. We think that postoperative mortality may decrease by revealing the factors in the preoperative, intraoperative and postoperative periods.
Keywords: Pancreaticoduodenectomy; postoperative mortality; prognosis